Monitoring of C‐reactive protein decreases length of stay after laparoscopic total mesorectal excision for cancer: a prospective case‐matched study in 236 patients. (23rd February 2021) - Cazelles, Antoine; Giacca, Massimo; Monsinjon, Marie; Hain, Elisabeth; Frontali, Alice; Panis, Yves
Abstract: Aim: The aim of this study was to evaluate a discharge strategy driven by monitoring of C‐reactive protein (CRP) in a homogeneous group of patients undergoing laparoscopic total mesorectal excision with sphincter‐saving surgery for rectal cancer (TME). Method: One hundred and thirteen patients who underwent a TME had CRP monitoring on postoperative day (POD) 5. Patients were discharged on POD 6 if the CRP level was ≤100 mg/L. Patients were matched (according to age, gender, body mass index, neoadjuvant pelvic irradiation and type of anastomosis) to 123 control patients who underwent the same operation with the same postoperative care but without CRP monitoring. Results: Postoperative 3‐month overall [CRP group 62/113 (55%) vs controls 73/123 (59%); p = 0.487] and severe (i.e. Clavien–Dindo grade 3 and above) [CRP group 17/113 (15%) vs controls 19/123 (15%); p = 0.931] morbidity rates were similar between groups. Mean length of hospital stay (LHS) was significantly shorter in the CRP group (CRP group 9.7 ± 14 days vs controls 11.6 ± 7 days; p < 0.001). Discharge occurred on POD 6 in 55/113 (49%) patients from the CRP group vs 7/123 (6%) from the control group ( p < 0.001). The rehospitalization rate [CRP group 19/113 (17%) vs controls 13/123 (11%); p = 0.177] was similar between groups. The CRP level on POD 5 had a diagnostic property to assess an anastomotic leakage with an area under the curve of 0.81. Conclusion: In patients who underwent TME, a discharge strategy based on CRP monitoring significantly decreased LHS without increasing morbidity, mortality or rehospitalization rates.